Human Epididymis Protein 4: A Novel Serum Inflammatory Biomarker in Cystic Fibrosis - Nagy, Jr, Béla; Nagy, Béla; Fila, Libor; Clarke, Luka A; Gönczy, Ferenc; Bede, Olga; Nagy, Dóra; Újhelyi, Rita; Szabó, Ágnes; Anghelyi, Andrea; Major, Miklós; Bene, Zsolt; et al. (Chest, 2016)
Increased expression of the human epididymis protein 4 (HE4) was previously described in lung biopsy samples from patients with cystic fibrosis (CF). It remains unknown, however, whether serum HE4 concentrations are elevated in CF. Seventy-seven children with CF from six Hungarian CF centers and 57 adult patients with CF from a Czech center were enrolled. In addition, 94 individuals with non-CF lung diseases and 117 normal control subjects with no pulmonary disorders were analyzed. Serum HE4 levels were measured by using an immunoassay, and their expression was further investigated via the quantification of HE4 messenger RNA by using quantitative reverse transcription polymerase chain reaction in CF vs non-CF respiratory epithelium biopsy specimens. The expression of the potential regulator miR-140-5p was analyzed by using an UPL-based quantitative reverse transcription polymerase chain reaction assay. HE4 was measured in the supernatants from unpolarized and polarized cystic fibrosis bronchial epithelial cells expressing wild-type or F508del-CFTR. Median serum HE4 levels were significantly elevated in children with CF (99.5 [73.1-128.9] pmol/L) compared with control subjects (36.3 [31.1-43.4] pmol/L; P < .0001). This observation was replicated in adults with CF (115.7 [77.8-148.7] pmol/L; P < .0001). In contrast, abnormal but lower HE4 concentrations were found in cases of severe bronchitis, asthma, pneumonia, and bronchiectasis. In patients with CF, the concentrations of HE4 were positively correlated with overall disease severity and C-reactive protein concentrations, whereas a significant inverse relationship was found between HE4 and the spirometric FEV1 value. Relative HE4 mRNA levels were significantly upregulated (P = .011) with a decreased miR-140-5p expression (P = .020) in the CF vs non-CF airway biopsy specimens. Twofold higher HE4 concentrations were recorded in the supernatant of polarized F508del-CF transmembrane conductance regulator/bronchial epithelial cells compared with wild-type cells. HE4 serum levels positively correlate with the overall severity of CF and the degree of pulmonary dysfunction. HE4 may thus be used as a novel inflammatory biomarker and possibly also as a measure of treatment efficacy in CF lung disease.